Protein Hydrolysis by Subcritical Water: A New Perspective on Obtaining Bioactive Peptides - Carlos I. Rivas-Vela; Silvia L. Amaya-Llano; Eduardo Castaño-Tostado; Gustavo A. Castillo-Herrera (Molecules, 2021)
The importance of bioactive peptides lies in their diverse applications in the pharmaceutical and food industries. In addition, they have been projected as allies in the control and prevention of certain diseases due to their associated antioxidant, antihypertensive, or hypoglycemic activities, just to mention a few. Obtaining these peptides has been performed traditionally by fermentation processes or enzymatic hydrolysis. In recent years, the use of supercritical fluid technology, specifically subcritical water (SW), has been positioned as an efficient and sustainable alternative to obtain peptides from various protein sources. This review presents and discusses updated research reports on the use of subcritical water to obtain bioactive peptides, its hydrolysis mechanism, and the experimental designs used for the study of effects from factors involved in the hydrolysis process. The aim was to promote obtaining peptides by green technology and to clarify perspectives that still need to be explored in the use of subcritical water in protein hydrolysis.